PENGARUH PENDEKATAN PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Nurul Sholehah (Mat-Edukasia, 2019)
This research is motivated by the low ability of students to solve mathematical problems. Judging from the initial tests of problem solving abilities, there are several indicators of problem solving abilities that cannot be achieved by students. This is because students only listen to what the teacher explains without understanding it, so students have not been able to solve mathematical problems. To overcome this, the researchers used a problem solving approach. This study aims to determine and describe the effect of the problem solving approach on students' mathematical problem solving abilities. This type of research is quantitative research with experimental methods, the research design is post test only control design. The population in this study were eighth grade students of Merangin Middle School 7 consisting of 3 classes. The sampling technique uses Simple Random Sampling, the selected sample is Class VIII A as the experimental class and Class VIII C as the control class. The data analysis technique used to test hypotheses is the t-test. From the final test data analysis in the experimental class obtained an average of 73.82, while the control class obtained an average of 63.13. Then the data were analyzed using t-test, because the data were normally distributed and homogeneous in variance. Hypothesis test results obtained, = 2.738 and = 1.678. Because> then Ho is rejected and Haa is accepted. So it can be concluded that there is an influence of the problem solving approach to the mathematical problem solving ability of students of class VIII SMP N 7 Merangin.